ORDINARY KRIGING GEOSTATISTICAL MODEL FOR LAND VALUE ZONING: A SPATIAL STUDY IN RANTAU PULUNG, EAST KALIMANTAN - Nanda Khoirunisa; Nola Lita Hutabarat; Carissa Aulia Maheswari (Elipsoida : Jurnal Geodesi dan Geomatika, 2026)
Land is a crucial element whose use is closely tied to spatial planning and regional management. This study aims to estimate the distribution of land values in Rantau Pulung District, East Kutai Regency, using the Ordinary Kriging geostatistical method. The main problem raised is the limited information on land values in areas that lack sample points. Primary data were obtained from 343 sample points of land prices from field surveys, while secondary data in the form of administrative boundaries were used as spatial references. The analysis was carried out using ArcGIS software with a spherical variogram model, which was selected as the best approach based on cross-validation results. The mapping results show that the highest land values are around main road access and activity centers, while the lowest prices are spread across less accessible outlying areas. This finding confirms that accessibility and proximity to public service centers are dominant factors in influencing land values. This interpolation map can be used as a basis for spatial planning, zoning, and more efficient land management policies.